Mutation breeding, genetic diversity and crop adaptation to climate change - Sivasankar, Sobhana; Ellis, Thomas Henry Noel; Jankuloski, Ljupcho; Ingelbrecht, Ivan (CABI, 2021)
This book presents reviews on the application of the technology for crop improvement towards food and nutrition security, and research status on mutation breeding and associated biotechnologies in both seed crops and vegetatively propagated crops. It also presents perspectives on the significance of next-generation sequencing and bioinformatics in determining the molecular variants underlying mutations and on emerging biotechnologies such as gene editing. Reviews and articles are organized into five sections in the publication: (1) Contribution of Crop Mutant Varieties to Food Security; (2) Mutation Breeding in Crop Improvement and Climate-Change Adaptation; (3) Mutation Induction Techniques for Enhanced Genetic Variation; (4) Mutation Breeding in Vegetatively Propagated and Ornamental Crops; and (5) Induced Genetic Variation for Crop Improvement in the Genomic Era. The contents of this volume present excellent reference material for researchers, students and policy makers involved in the application of induced genetic variation in plants for the maintenance of biodiversity and the acceleration of crop adaptation to climate change to feed a growing global population in the coming years and decades.